1996
DOI: 10.1177/0148607196020003187
|View full text |Cite
|
Sign up to set email alerts
|

IV Chenodeoxycholate Prevents Calcium Bilirubinate Gallstones During Total Parenteral Nutrition in the Prairie Dog

Abstract: IV CDC is effective in preventing TPN-associated gallstones in the prairie dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Sinealide (cholecystokinin) that was used in 5 human studies, failed to show longterm effects in preventing and treating PN-associated gallbladder disease [595e597]. In animal studies it has been observed that intravenous chenodeoxycholate prevents calcium bilirubinate gallstones [598] and glutamine-enriched total PN prevents the lithogenic effect of PN [599]. In practice, the major recommendation for preventing biliary sludge or stone formation is to encourage oral and/or enteral feeding as fast as possible.…”
Section: Prevention/treatment Of Gallbladder Sludge and Stonesmentioning
confidence: 99%
“…Sinealide (cholecystokinin) that was used in 5 human studies, failed to show longterm effects in preventing and treating PN-associated gallbladder disease [595e597]. In animal studies it has been observed that intravenous chenodeoxycholate prevents calcium bilirubinate gallstones [598] and glutamine-enriched total PN prevents the lithogenic effect of PN [599]. In practice, the major recommendation for preventing biliary sludge or stone formation is to encourage oral and/or enteral feeding as fast as possible.…”
Section: Prevention/treatment Of Gallbladder Sludge and Stonesmentioning
confidence: 99%
“…Thus, correction of gallbladder stasis by exogenous cholecystokinin prevents sludge and gallstones in these patients [44]. Pigment stones are also common in liver cirrhosis and chronic haemolytic conditions such as beta-thalassemia and sickle cell anaemia [11][12][13][14][15][16][17][18]38]. It is of interest that impaired gallbladder motility has been reported in liver cirrhosis [10][11][46][47], sickle cell anaemia [18] and beta-thalassemic children [17].…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about gallbladder motorfunction in patients with pigment stones, whose pathogenesis differs from that of cholesterol gallstones [9]. The presence of impaired gallbladder motility has been previously reported in conditions associated with formation of pigment stones such as liver cirrhosis [10][11][12][13], total parenteral nutrition [11][12][13][14][15][16], beta-thalassemia [17] and sickle cell haemoglobinopathy [18]. However, information on gallbladder motility in patients presenting with black 'primary' pigment gallstones is still incomplete; moreover, virtually all studies lack an exact characterization of gallstones and biliary cholesterol crystallization in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A separate study done by Broughton et al found that IV administration of CDCA reduced TPN induced pigmented gallstones in prairie dogs. Six prairie dogs given IV CDCA on TPN for roughly 40 days had no gallstones compared to all of the TPN prairie dogs which all had gallstones [ 109 ]. Many other studies have found improvements in gut function or hepatoprotection related to TPN injury by addition of other bile acids or components of bile such as taurine, tauroursodeoxycholic acid, or oleanolic acid [ 26 , 110 , 111 ] ( Table 1 ).…”
Section: Novel Therapeutics ( Table 1 )mentioning
confidence: 99%